Pharmacokinetics of Oral and Intravenous Oseltamivir Treatment of Severe Influenza B Virus Infection Requiring Organ Replacement Therapy - Karsch, Katharina; Chen, Xi; Miera, Oliver; Peters, Bjoern; Obermeier, Patrick; Francis, Roland C. E.; Amann, Valerie; Duwe, Susanne; Fraaij, Pieter; Heider, Alla; De Zwart, Marcel; Berger, Felix; et al. (European Journal of Drug Metabolism and Pharmacokinetics, 2017)
Background and Objectives: Patients with severe influenza virus infection, multi-organ failure and organ replacement therapy may absorb and metabolize neuraminidase inhibitors differently. Systematic pharmacokinetic/pharmacodynamic clinical trials are currently lacking in this high-risk group. Inadequate dosing increases the risk of treatment failure and drug resistance, especially in severely ill patients with elevated virus loads. This study aims to explore the impact of organ replacement therapy on oseltamivir drug concentrations. Methods: Serial pharmacokinetic/pharmacodynamic measurements and Sieving coefficients were assessed in two patients with severe influenza B infection requiring organ replacement therapy. Results: Patient #1, a 9-year-old female with severe influenza B virus infection, biventricular assist device, and continuous veno-venous hemodiafiltration, received 75 mg oral oseltamivir twice-daily for 2 days, then intravenous oseltamivir with one-time renoprotective dosing (40 mg), followed by regular intravenous administration of 100 mg twice-daily. Plasma oseltamivir carboxylate concentrations were stable initially, but only regular administration of 100 mg resulted in virus load decline and clinical improvement. Patient #2, a 28-year-old female with influenza B virus infection requiring extracorporeal membrane oxygenation, received 75 mg oral oseltamivir twice-daily, resulting in erratic oseltamivir blood concentrations. In both patients, drug concentrations remained well within safety margins. Conclusions: In severe cases with multi-organ failure, administration of 100 mg intravenous oseltamivir twice-daily provided reliable drug concentrations, as opposed to renoprotective and oral dosing, thereby minimizing the risk of treatment failure and drug resistance. Evidence-based pediatric dosing recommendations and effective intravenous antiviral treatment modalities are needed for intensive care patients with life-threatening influenza disease.
CRIS-Team Scopus Importer:2022-11-17